Bamboo cellulose nanofibrils as potentialphenol-formaldehyde adhesive reinforcement in engineered bamboo plank application. - Lebrillo, Kynn O. (2024.)
Synthetic adhesives such as phenol-formaldehyde (PF) adhesive, is valued for their exceptional thermal resistance in adhesive properties. However, their widespread use is often faced with drawbacks which includes their brittleness and formaldehyde emission. Fortunately, advancement in nanotechnology enables reinforcements with cellulose nanofibrils (CNF) which possesses several characteristics that address the limitations of PG resins. With this, CNF was synthesized from waste bamboo sawdust with nanoscale diameters and high aspect ratio. CNF is added to PF resins to synthesize CNF-reinforced PF (CNF-PF) adhesive. Fourier transform infrared (FTIR) spectroscopy confirms the incorporation of CNF in PF matrix, proving that CNF-PF adhesive has been successfully synthesized. Parametric study was also conducted to determine the effects of CNF concentration, mixing time, and mixing temperature on the CNF-PF shear strength. It was determined that an increase in CNF concentration has a negative effect on CNF-PF shear strength while increasing mixing time and mixing temperature has a positive effect. The interaction of the three parameters also has a significant effect on CNF-PF shear strength. A model equation with an R2 of 0.7842 was also generated to describe the behavior of each factor on CNF-PF shear strength, as well as to predict possible new observations. Model validation was also conducted which confirms the validity of the model equation in determining the shear strength of new observation at 95% confidence level. Comparison of CNF-PF and pure PF adhesive was enhanced by 37.5%, demonstrating a substantial improvement in mechanical performance. These findings collectively suggest that CNF serves as highly effective reinforcement materials for material reinforcement in phenol-formaldehyde adhesive.
Thesis (Undergraduate, Bachelor of Science in Chemical Engineering) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2024.
Keywords: Bamboo plank